Postoperative pyoderma gangrenosum at trocar site following laparoscopic cholecystectomy in a patient with acute myeloid leukemia: a very rare case report - Georgiou, Chrysanthos; Lambrou, Georgios; Modestou, Christalla (International Surgery Journal, 2025)
Pyoderma gangrenosum (PG) is a rare neutrophilic dermatosis that may be triggered by surgical trauma, often mimicking postoperative wound infection. Early recognition is essential to avoid unnecessary surgical interventions. Herein this report presents the case of a 71-year-old male with a history of acute myeloid leukemia in remission who underwent laparoscopic cholecystectomy for symptomatic cholelithiasis. Despite initial postoperative recovery, he presented on postoperative day 12 with erythema and purulent discharge from a trocar site. Imaging suggested a postoperative collection, but cultures remained negative, and skin ulceration progressed despite broad-spectrum antibiotics. Two skin biopsies were required to establish the diagnosis of PG. The patient responded favorably to systemic corticosteroids. This case highlights the importance of considering postoperative PG in patients with rapidly progressive ulcerative lesions unresponsive to antibiotics, particularly in individuals with underlying hematologic disease. Early biopsy and multidisciplinary evaluation are crucial to timely diagnosis and appropriate management.